2016
DOI: 10.3389/fpsyg.2016.01829
|View full text |Cite
|
Sign up to set email alerts
|

Mother-Child Play: A Comparison of Autism Spectrum Disorder, Down Syndrome, and Typical Development

Abstract: The purpose of the present study was to analyze mother-child collaborative play in children with Autism Spectrum Disorders (ASD) compared to children with Down Syndrome (DS) and typical developing children (TD). Children with ASD are often described as having deficient play skills, particularly in the symbolic domain. Caregivers’ involvement in child play activities increases the structural complexity of playing in both typically developing children and children with disabilities. Participants included 75 moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 55 publications
(92 reference statements)
3
17
0
3
Order By: Relevance
“…Notably, most of these studies provided micronutrient supplementation and play materials whereas we educated the mothers without supporting them with either food or toys. Mother-child play interaction models promote children’s engagement in several activities that enhance development [32]. Moreover, our findings are in accordance with a previous Ugandan study which reported slightly higher cognitive scores three months after stimulation and nutrition education [20].…”
Section: Discussionsupporting
confidence: 91%
“…Notably, most of these studies provided micronutrient supplementation and play materials whereas we educated the mothers without supporting them with either food or toys. Mother-child play interaction models promote children’s engagement in several activities that enhance development [32]. Moreover, our findings are in accordance with a previous Ugandan study which reported slightly higher cognitive scores three months after stimulation and nutrition education [20].…”
Section: Discussionsupporting
confidence: 91%
“…In relation to exploratory play, no marked differences were found between the groups in the present sample. This finding is also confirmed by other studies (Baranek et al, 2005;Wilson et al, 2017) but comes in contrast to findings showing that children with ASD spend more time in exploratory play than TD children (Bentenuto et al, 2016;Dominguez et al, 2006).…”
Section: Discussionsupporting
confidence: 88%
“…Research shows the existence of a remarkable relationship among child play, the age of development [ 42 ], and the development of expressive and receptive language [ 41 , 43 , 44 , 45 , 46 , 47 ] in children with both typical and atypical development. According to Bigham [ 37 ], the delay in the development of language and receptive language predicts the difficulties of children with ASD in pretend play.…”
Section: Introductionmentioning
confidence: 99%